Regulisanje pitanja državne imovine i vladavina prava – da li je Ustavni sud BiH otišao predaleko? / Regulation of State Property and Rule of Law - Was the Constitutional Court of BiH going too far? - Nurkić, Benjamin; Hasanović, Faris (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The aim of this paper is to consider the relationship between the regulation of state property and the rule of law, and for this purpose the authors analyze the Decision of the Constitutional Court of BiH No. U-4/21 which declared certain provisions of the Law on Forests of Republika Srpska unconstitutional. The paper discusses not only the issues of the relationship between state property and the rule of law, but also the issues of judicial activism and the rule of law. In particular, the authors analyze the extent to which the courts, and in this particular case the Constitutional Court of BiH, in order to protect the rule of law, may interfere in the competences of the legislature. In this context, the authors consider the justification of judicial activism of the Constitutional Court of BiH in case U-4/21, considering whether the Constitutional Court of BiH has the right to protect the principle of the rule of law in such a way. Finally, the authors explain why judicial activism is necessary when it comes to the relationship between constitutional and legislative power and why judicial activism of the BiH Constitutional Court was necessary in the case U-4/21.